2015
DOI: 10.1016/j.phrs.2015.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of positively charged triazine antagonists of prokineticin receptors on the transient receptor vanilloid type-1 (TRPV1) channel

Abstract: Four positively charged compounds, previously shown to produce analgesic activity by interacting with prokineticin receptor or T-type calcium channels, were tested for their ability to inhibit capsaicin-induced elevation of intracellular Ca(2+) in HEK-293 cells stably transfected with the human recombinant TRPV1, with the goal of identifying novel TRPV1 open-pore inhibitors. KYS-05090 showed the highest potency as a TRPV1 antagonist, even higher than that of the open-pore triazine inhibitor 8aA. The latter sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…KYS-05090S did not have any further effects in Cav3.2 null mice, indicating that its mechanism of action is dependent on this T-type channel isoform. This result is somewhat surprising since, in addition to its effect on Cav3.2, KYS-05090S has also been shown to inhibit native TRPV1 channels in vitro [8] and is also able to block recombinant Cav2.2 channels with an affinity of ∼5 μM [26], both of which are known targets for analgesics. In particular, it is well established that TRPV1 is a major Asterisks denote the significance relative to the control group (Cav3.2+/+ vehicle); ***P<0.001 (one-way ANOVA followed by Tukey's test).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…KYS-05090S did not have any further effects in Cav3.2 null mice, indicating that its mechanism of action is dependent on this T-type channel isoform. This result is somewhat surprising since, in addition to its effect on Cav3.2, KYS-05090S has also been shown to inhibit native TRPV1 channels in vitro [8] and is also able to block recombinant Cav2.2 channels with an affinity of ∼5 μM [26], both of which are known targets for analgesics. In particular, it is well established that TRPV1 is a major Asterisks denote the significance relative to the control group (Cav3.2+/+ vehicle); ***P<0.001 (one-way ANOVA followed by Tukey's test).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, targeting multiple types of ion channels that are involved in the processing of pain signals may be a useful strategy for the development of new pain therapeutics. A recent series of studies has reported on both in vitro and in vivo effects of a series of 3,4-dihydroquinazoline derivatives [8,26]. One of the derivatives, KYS-05090S (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…One such study treated mice with a selective TRPV1 antagonist, A-889425, and identified a corresponding blockade of pain-relaying A-delta nerve fibers, indicating a potential avenue for novel nociceptive modulation [31]. Another group discovered a highly selective an potent antagonist, KYS-05090, to TRPV1 and proposed potential clinical utility [32]. Finally, antibodies directed against TRPV1 channels have been developed [33].…”
Section: Transient Receptor Potential Cation Channel (Trp) Pharmacmentioning
confidence: 99%
“…In particular, DCs express TRPV1. And evidence suggests that TRPV1 modulates maturation of DCs through AMPK activation (Baskaran, Krishnan, Ren, & Thyagarajan, 2016;Ching et al, 2012;De Petrocellis et al, 2015; B. H. Li et al, 2014;Omari, Adams, & Geraghty, 2017).…”
Section: Introductionmentioning
confidence: 99%